Early Modern Ireland and the world of medicine Practitioners, collectors and contexts - Cunningham, John (Social Histories of Medicine, 2019)
This collection of essays offers important new insights across a range of topics relating to medicine in early modern Ireland. Of particular note is the substantial attention devoted to the often neglected period before 1750. Among the key subjects addressed by the contributors are Gaelic medicine, warfare, the impact of new medical ideas, migration, patterns of disease, midwifery and childbirth, book collecting, natural history, and urban medicine. The twelve essays effectively situate Irish medicine in relation to long-term social and cultural change on the island, as well as to appropriate international contexts; British, European and Atlantic. Early Modern Ireland and the world of medicine brings together a selection of established scholars as well as early career historians. It will be of interest to academics and students of the history of early modern medicine. It also contains much that will be essential reading for historians of Ireland.